The Competitiveness of Poland on the Environmental Products and Services Market; KonkurencyjnosćṔolski na rynku towaroẃ i usług sŕodowiskowych - Zofia Wysokinśka (Comparative Economic Research. Central and Eastern Europe, 2009)
The aim of the paper is to present main aspects related to the characteristics of the market of environmental goods and services as one of the most potentially fast developing markets in the world economy (among such markets with similar size as, the pharmaceuticals and information technology markets). The paper will also examine some effects of environmental measures on market access within the multilateral liberalization process. This is a very positive phenomenon in this age of ever increasing attention paid to the implementation of principles of sustainable development as well as decreased barriers for improving access to developing markets in the case of both economically highly developed countries and in developing countries. The elimination of trade barriers in foreign trade for goods and services also increases the efficiency of the world economic system by enabling countries to specialize in those sectors in which they possess economic advantages, which includes those sectors in which they possess favorable natural environmental conditions. The analysis of these goods and services is related also to some regulations of the Committee for Trade and Environment of the WTO with special reference to conclusions of the Fourth and Fifth Ministerial Conferences in Doha and Cancun. Poland has relatively small, but still growing position in the analyzed market. As a member of the European Union, Poland should side with an acceleration in negotiations relating to the quick opening up of environmental services markets within the framework of the Doha Round. – – Celem artykułu jest prezentacja głoẃnych aspektoẃ zwiazanych z charakterystyka rynku towaroẃ i usług sŕodowiskowych, jako jednego z najszybciej rozwijajacych sie rynkoẃ w gospodarce sẃiatowej (zblizȯnego pod tym wzgledem do rynku farmaceutycznego oraz rynku technologii informacyjnych i komunikacyjnych). W artykule analizowane sa wybrane efekty miernikoẃ sŕodowiskowych z punktu widzenia dostepu do rynku w ramach ponadnarodowych procesoẃ liberalizacyjnych Pozytywnym zjawiskiem jest przywiazywanie coraz wiekszej uwagi do kwestii zroẃnowazȯnego rozwoju jak roẃniezḋazėnie do zmniejszenia wysokosći barier ograniczajacych dostep do rynkoẃ w krajach rozwijajacych sie. Stopniowa eliminacja barier na towary i usługi sŕodowiskowe w handlu zagranicznym zwieksza efektywnosćśẃiatowego systemu ekonomicznego pozwala na specjalizacje w tych sektorach, w ktoŕych osiagania jest przewaga konkurencyjna i w ktoŕych posiadane sa naturalne sprzyjajace warunki do rozwoju. Analiza towaroẃ i usług sŕodowiskowych odnosi sie do regulacji rekomendowanych przez Komitet Handlu i Sŕodowiska Sẃiatowej Organizacji Handlu (WTO), ze szczegoĺnym uwzglednieniem postanowienÍV I V Miedzynarodowej Konferencji Ministerialnej w Doha i Cancum. Polska ma stosunkowo niewielka, ale rosnaca pozycje w analizowanym rynku. Jako kraj członkowski Unii Europejskiej, powinna bycźainteresowana szybkim otwarciem rynku usług sŕodowiskowych w ramach Rundy Doha.
Keywords: 330